HEAVY MEALS IN URBAN ROADSIDE SOILS, PART 1: EFFECT OF PARTICLE SIZE FRACTIONS ON HEAVY METALS PARTITIONING - Wang X.; Qin Y.; Chen Y. (My University, 2006)
Urban roadside soils are important environmental media for assessing heavy metal concentrations in urban environment. However, among other things, heavy metal concentrations are controlled by soil particle grain size fractions. In this study, two roadside sites were chosen within the city of Xuzhou (China) to reflect differences in land use. Bulk soil samples were collected and then divided by particle diameter into five physical size fractions, 500–250, 250–125, 125–74, 74–45, < 45 μm. Concentrations of metals (Ti, Cr, Al, Ga, Pb, Ba, Cd, Co, Cu, Mn, Ni, V, Zn, Mo, As, Sb, Se, Hg, Bi, Ag) were determined for each individual fraction. These metals could be roughly classified into two groups: anthropogenic element (Pb, Ba, Cd, Cu, Zn, Mo, As, Sb, Se, Hg, Bi, Ag) and lithophile element (Ti, Cr, Al, Ga, Co, Mn, Ni, V) in terms of values of enrichment factor. As expected, higher concentrations of anthropogenic heavy metals (Cu, Zn, Mo, As, Hg, Bi, Ag) are observed in the finest particle grain size fraction (i.e. < 45 μm). However, heavy metals Se, Sb and Ba behave independently of selected grain size fractions. From the viewpoint of mass loading, more than 30% of the concentrations for all anthropogenic heavy metals are contributed by the particle grain size fractions of 45–74 μm at site 1 and more than 70% of the concentrations for all heavy metals are contributed by the particle grain size fractions of 45–74 and 74–125 μm at site 2. These results are important for transport of soil-bound heavy metals and pollution control by various remedial options.
Keywords: GRAIN SIZE FRACTION; HEAVY METAL PARTITIONING; URBAN ROADSIDE SOILS; LOADING; XRD; XUZHOU; CHINA